Ethnic minority patients not at increased risk of adverse events during hospitalisation in urban hospitals in the Netherlands: results of a prospective observational study. Issue 12 (30th December 2014) - van Rosse, Floor; Essink-Bot, Marie-Louise; Stronks, Karien; de Bruijne, Martine; Wagner, Cordula
Abstract : Objectives: We analysed potential differences in incidence, type, nature, impact and preventability of adverse events (AEs) during hospitalisation between ethnic Dutch and ethnic minority patients, and the role of patient-related determinants. We hypothesised an increased AE incidence for ethnic minority patients. Setting: We conducted a prospective cohort study in four urban hospitals. Participants: 763 Dutch patients and 576 ethnic minority patients aged between 45 and 75, admitted for at least one night, were included in the study. All patients completed a questionnaire on patient-related determinants (eg, language proficiency). Outcome measures: Incidence, type (eg, diagnostic AEs), impact and nature of AEs were assessed with a two-stage medical record review. Logistic regression analysis was used to adjust for patient and admission characteristics, and to investigate the contribution of patient-related determinants to AE risk. Results: There was no significant difference in the incidence of AEs: 11% (95% CI 9% to 14%) in Dutch patients and 10% (95% CI 7% to 12%) in ethnic minority patients. Also, there was no significant difference in the incidence of preventable AEs: 3% (95% CI 1% to 4%) in Dutch patients and 1% (95% CI 0% to 2%) in ethnic minority patients. Low language proficiency, inadequate health literacy and low educational level did not increase the risk of an AE. Conclusions: Compared with Dutch patients, ethnic minority patients were not at increased risk of AEs while receiving care in Dutch hospitals. Healthcare providers seem to have responded effectively to specific patient care needs, but we do not know whether this occurred in an ad hoc or in a systematic way.